AB0580 Clinical characteristics and risk factors of behcet's patients with conduction disturbances-data from a cardiovascular clinical center in china. (15th June 2017) - Bai, R; Gao, N
Abstract : Background: Behcet's disease is a kind of systemic vasculitis affecting multiple systems. Although symptomatic cardiac involvement in Behcet's disease is uncommon, the fatality rate may reach up to 29%. Conduction disturbances might lead to poor outcome and often need permanent pacemaker implanted. The characteristics of conduction disturbances in Behcet's disease were rarely reported before. Objectives: To investigate the clinical characteristics of Behcet's patients with conduction disturbances and explore the underlying risk factors. Methods: We reviewed 57 medical records of Behcet's disease with cardiovascular lesions in Anzhen Hospital, Capital Medical University between January 2002 and July 2015, and analyzed the clinical characteristics. Results: (1) There were 13 patients with conduction disturbances out of a total of 57 Behcet's disease cases (22.8%) in our research: three patients with first-degree atrioventricular block; one patient with Mobtizs type I second- degree atrioventricular block; four patients with third-degree atrioventricular block; one patient with the left anterior branch block; one patient with complete right bundle branch block; three patients with first-degree atrioventricular block combined with the left anterior branch block or complete right bundle branch block. One patient (7.7%) died from infectious endocarditis and aortic root abscess during hospital stay. (2) Hemoglobin level was significantly lower in cases than controls (111.23±23.06 vs. 127.16±19.86 g/L, P=0.017); The median of albumin level in cases was higher than controls [34.5 (14.2) vs. 38.5 (9.9) g/L, P=0.032] (Table 1); C reactive protein level was higher in cases than controls [26.12 (21.3) vs. 6.7 (16.4) mg/L, P=0.045] (Table 1). (3) The aortic valvular insufficiency presented more frequently in patients in the case group than the control group (92.3% vs. 47.7%, respectively; P=0.004).Heart reconstruction can be seen in Behcet'patients with cardiac involvement. The echocardiography showed the following parameters were significantly different between two groups: left ventricular end-diastolic diameter (64.85±10.96 vs. 52.55±10.13 mm, P=0.001); left ventricular end-contraction diameter [48 (15) vs. 31 (13) mm, P=0.001]; left atrial diameter [50 (17) vs. 35.85 (13) mm, P=0.003]; outflow tract of right ventricle [26 (7) vs. 27 (6) mm, P=0.045] (4) Aortic valvular insufficiency was an independent risk factor for Behcet's disease with conduction disturbances (OR =1.157, 95% CI 1.034, 1.293, P=0.011). Conclusions: Behcet's disease is one of the unusual etiologies of atrioventricular block. The evaluation of conduction disturbance should be kept in mind when diagnosing BD's patient. References: Desbois A C, Wechsler B, Cluzel P, et al.: Cardiovascular involvement in Behcet's disease.Rev Med Interne 2014; 35(2):103–111. Braunwald E, Fauci A.S, Kasper D, et al.: Harrison's principles of international medicine. New York: McGraw-Hill 2001, 1287. Butt SU, McNeil J.: Complete heart block in a Caucasian woman with Behçet's disease: a case report. J Med Case Rep 2016;19;10:102. Gao N, Han W, Ci WP, et al.: Clinical data analysis of cardiovascular involvement in Behcet's disease. Zhonghua Yi Xue Za Zhi 2016, 24;96(19):1523–6. Disclosure of Interest: None declared